Second Language Acquisition of Constraints on WH-Movement by L2 English Speakers: Evidence for Full-Access to Syntactic Features - Hettiarachchi, Sujeewa; Pires, Acrisio (Languages (Basel), 2022)
This paper presents results from two experiments on the L2 acquisition of wh-features and relevant constraints (Superiority and Subjacency) by L1 Sinhala–L2 English speakers. Our results from a Truth Value Judgment Task and a Grammaticality Judgment Task with 31 English native controls and 38 Sinhala/English bilinguals show that the advanced adult L2 speakers of English we tested have successfully acquired the uninterpretable wh-Q feature and relevant movement constraints in English, despite the lack of overt wh-movement in L1-Sinhala. These results raise questions for Representational Deficit Accounts of second language acquisition and offer evidence that (i) uninterpretable syntactic features are not necessarily subject to an early critical period and (ii) uninterpretable features not instantiated in learners’ L1 can be available for L2 syntactic computation. We take our results as evidence for full access by L2 learners to syntactic properties that are not instantiated in their L1, but that remain accessible due to a cognitive capacity for language (i.e., knowledge of Universal Grammar) independently of the L1.